Real Effective Exchange Rate and Trade Balance Adjustment : The Case of Turkey - Iossifov, Plamen (IMF Working Papers; Working Paper ;, 2019)
There is an ongoing debate in the literature on whether global trade flows have become disconnected from the large real effective exchange rate movements in the wake of the global financial crisis. The question has important policy implications for the role of exchange rates in supporting growth and restoring external balance. In this paper, we use Turkey---a large and open emerging market economy that has experienced sizable swings of the real effective exchange rate---as a case study to test competing hypotheses. Our results lend support to the finding in existing cross-country studies that the real effective exchange rate remains an important determinant of trade flows. But, its effect is not symmetric in secular periods of appreciation and depreciation and is, oftentimes, dwarfed by the impact on trade flows of the income growth differential between trade partners.